ANALISIS MOTIVASI BIDAN PRAKTEK MANDIRI (BPM) DALAM MEMBERIKAN PELAYANAN KESEHATAN IBU NIFAS DI KOTA SEMARANG - Arina Noor Eka Rachmawati; Ayun Sriatmi; Septo Pawelas Arso (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
Maternal mortality rate in Semarang in 2015 is 128,5/100.000 live births by the largest percentage in puerperium (74.29%). Most deaths occurred in the KF2 and KF3 where the mother's position is already at home. The coverage of KF3 is still not reached in accordance with the government’s target as many as 86,91%. This is possible because of the lack of motivation BPM to monitor the condition of the mother during puerperium. The purpose of this research was to analysis how far motivation of BPM when providing postpartum maternal health sevices. This research uses a qualitative method with indepth interviews to 6 BPM. Results showed that hopes can forced BPM to providing services because BPM will get satisfaction, pleasure, tranquility, appreciated, respected, helpful to others, trusted also can increase financial income. Its also can make the personal needs fulfilled, such as felt protected and cherished by people around, more confident, and even get the chance to become a facilitator of Bidan Delima or head branch in the organization. But when facing obstacles, BPM will change their attitude into be annoyed and tend not perform her duty well. It also affects the persistence of BPM in providing services. So far, there is output of service that not achieved, such as have not been able to change mindset about the myths and the lack of number of visits. It is estimated due to the lack of sacrification in providing services. IBI Semarang should improve supervision and coordination to motivate BPM in providing postpartum meternal health care services.